2012
DOI: 10.1108/02686901211228002
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of audit fees and fraud classification: impact of SOX

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…The size variable is not significantly different since the control firms were matched based on size and industry. The qualified opinion, sales/total assets, growth (which is a similar measure to sales/total assets), and fee ratios are not significant as in previous empirical studies such as Krishnan et al (1996) and Lenard et al (2011).…”
Section: Data Collection and Research Designmentioning
confidence: 45%
See 2 more Smart Citations
“…The size variable is not significantly different since the control firms were matched based on size and industry. The qualified opinion, sales/total assets, growth (which is a similar measure to sales/total assets), and fee ratios are not significant as in previous empirical studies such as Krishnan et al (1996) and Lenard et al (2011).…”
Section: Data Collection and Research Designmentioning
confidence: 45%
“…Recently, Boland et al (2015) found empirically that misstatements in financial reporting decreased with the later SOX filers. This issue will be important for auditors preparing audit planning procedures if they can predict that some firms may need more rigorous auditing and assessment of their internal control system and may need to charge higher audit fees (Lenard, Petruska, Alam, & Yu, 2011). Investors may demand more reliable financial information for their portfolio after SOX.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Vousinas, 2019) fraud will be much more difficult to stop when it occurs due to collusion either between employees, or employees and external parties. Lenard, Petruska, Pervaiz, & Yu (2012) found that the company's audit fees were higher in the before-during-after years of fraud litigation compared to companies without fraud cases. Even an increase in audit fees occurs when the auditor must consider the compensation obtained by management in planning the audit because of the potential risk of fraud arising from equity incentives (Kannan, Skantz, & Higgs, 2014).…”
Section: H2: Change In Director Has a Positive Effect On Financial St...mentioning
confidence: 94%
“…Melis (2005) analysed Parmalat's fraud case and concluded the company did not have independent directors. Lenard et al (2012) provide evidence of the association between the corporate governance structure's effectiveness and the external auditor assessing fraud risk.…”
Section: Board Characteristics Composition and Structurementioning
confidence: 99%